2021
DOI: 10.1108/mrr-09-2020-0598
|View full text |Cite
|
Sign up to set email alerts
|

Can adaptive–academic leadership duo make universities ready for change? Evidence from higher education institutions in Pakistan in the light of COVID-19

Abstract: Purpose In rapidly changing global village, individuals, organizations and the society are faced with various unforeseen challenges every day, and these challenges continuously trigger and test the instincts for survival, and higher education is of no exception. In the context of today’s most critical uncertainty, i.e. COVID-19, the purpose of this study is to highlight the significance of two leadership styles, i.e. adaptive and academic leadership, and assessing readiness for change among higher education in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 82 publications
1
13
0
1
Order By: Relevance
“…As hypothesized, the study found a significant negative relationship between agile leadership and work–family conflicts and family–work conflicts, which are also supported by studies conducted by Akkaya et al (2020) and Jia and Li (2022) . In Pakistani context, research suggests that academic and adaptive leadership helped implement change and develop higher education institutes ( Mukaram et al, 2021 ). For instance, in Pakistan, HEC is dedicated to making e-learning success in the wake of the COVID-19 pandemic, COVID-19-specific policies and procedures and emergent levels of support helped leadership in educational institutes facilitate students and employees at the same time ( Mumtaz et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As hypothesized, the study found a significant negative relationship between agile leadership and work–family conflicts and family–work conflicts, which are also supported by studies conducted by Akkaya et al (2020) and Jia and Li (2022) . In Pakistani context, research suggests that academic and adaptive leadership helped implement change and develop higher education institutes ( Mukaram et al, 2021 ). For instance, in Pakistan, HEC is dedicated to making e-learning success in the wake of the COVID-19 pandemic, COVID-19-specific policies and procedures and emergent levels of support helped leadership in educational institutes facilitate students and employees at the same time ( Mumtaz et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Faculty found it difficult to be flexible enough to become tech savvy and adapt to the changing situations. It was difficult for educational institutions to match the internal pace of change with the external pace of change ( Mukaram et al, 2021 ). According to the W-HR model, as employees develop their resources such as elevated moods, better self-esteem, and positive emotional support, it has a significant impact on performance, as these resources help improve personal resources at work ( Ten Brummelhuis and Bakker, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is need to be effective administrative leadership style in changing educational environment. It has been stated that appropriate leadership style is required in diverse situations and behaviors of leaders in contingent situations, such as prior studies reported the role of adaptive leadership (Mukaram et al, 2021;Kozachuk & Conley, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The complexity inclined in education sector due to adoption of technological equipment for online sessions during covid19 that requires transformation at multiple ends. Therefore, the leadership in educational institutes and higher education sector must be changed to appropriate leadership style that is found to be necessary in educational institutes (Dee & Leišytė, 2016;Mukaram et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…В данной части исследования на основе результатов опроса родителей учеников начальной школы, участвующих в эксперименте 36 , отражена динамика их отношения к цифровизации в образовании детей.…”
Section: сравнительный анализ позиций родителейunclassified